Performance and emission effects of biodiesel 30% (B30) usage in oil-fired power plants and gas engine power plants. Issue 1 (May 2021) - Nina, Konitat S; Suntoro, Dedi; Irsyad, Muhammad Indra Al; Zulkarnain; Widhiatmaka; Srikandi, Gea Prita; Khaldun, T; Fauzi; Anggarani, Riesta; Faridha
Abstract: In 2020, Indonesia Government through the Ministerial Regulation of Energy and Mineral Resources No. 12 Year 2015 obligates the use of 30% biodiesel mixed diesel fuel (B30) for various sectors including the power generation sector. The obligation potentially affects the performance of oil-fired power plants (PLTD) and gas engine power plants (PLTMG) that are common power plant technologies used by the State-owned Electricity Company (PLN) in remote and disadvantaged areas. The objective of this study is to estimate effects of B30 usage on performance and emissions of PLTD and PLTMG. We compare performance and emission data of 3 (three) power plants before and after using B30. The results show that the uses of B30 increases spesific fuel consumption (SFC) by 0.009 L/kWh in PLTD and by 0.0071 L/kWh in PLTMG. The uses of B30 will reduce emissions of SO2, CO, and particulate matter, except NOx emission.